Principals' self-perception of their transformational leadership practices and its effects on Student academic performance in Sidama Region, Ethiopia. : School Principals Transformational leadership practices - Dukamo, Dessie Dalkie; RJ (Nico), Botha (Technium Education and Humanities, 2025)
Abstract The study examined principals' transformational leadership practices and how they can affect student academic performance in Ethiopia's Sidama region. It employed a convergent parallel mixed research design. The quantitative part of the study used a modified MLQ-based questionnaire, while the qualitative phase used an open-ended semi-structured interview. The study's dependent variable was student academic performance, while the independent variable was principals' transformational leadership practices. The study targeted 95 public secondary schools in Ethiopia's Sidama region. The study used an appropriate sample approach and included 91 principals from 24 public secondary schools. In the qualitative phase, ten principals took part. An analysis of the gathered data was done using both descriptive and inferential statistics. The study's findings demonstrated that principals comprehend and practice transformational leadership. Furthermore, the study showed that the principal's transformational leadership techniques significantly and favorably affect students' academic performance, with an overall correlation value of r =.827 (p<.01). The results of the linear multiple regression showed that 69.9% of the variation in the student's academic performance could be explained by modifications in the principal's transformational leadership approach. Furthermore, the study showed that principals in high-performing schools more frequently exhibit transformational leadership behaviors than in low-performing ones.